Analysis of Transhipment Policy on Long Line Fisheries Vessels Business Performance - Amelia Hudayana; Tiwi Nurjannati Utami (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
This research aims to know and to analyze the impact of transshipment policy on production and business performance of long line vessels, effectiveness of transshipment policy, and constrain factors on the policy implementation. Respondents of this research are 60 long line vessels with criteria above 50 GT. This research method use qualitative and quantitative descriptive. This research show that the implementation of transhipment policy reduce the catching fishery production by 15% and Tuna commodity by 26%. The impact of transhipment policy also reduce the business performance. This results show that sailing trip is decrease. Otherwise, catching tonage, sizing output and earning are decrease. Effectiveness of transhipment policy on the input and process with indicator of performance very good and so do the output. Constrain factors on implementation of transshipment policy are businessman can not fulfill standart product of freshness, otherwise there is regulation of fishery transhipment activities for carrying fishing vessels yet.